Assessing Producers’ Knowledge in Good Manufacturing Practices during the Production of a Traditionally Fermented Food (Ga Kenkey) in the Ho Municipality, Ghana - Felix Kwashie Madilo; Emmanuel Letsyo; Bless Abrah Oppong; Yayra Benedicta Buachi; Comfort Mawuse Klutse; Angela Parry-Hanson Kunadu (Journal of Food Quality)
Good manufacturing practice (GMP) is the primary sanitary and processing requirement necessary to ensure the production of safe foods. It ensures that the production facilities and processes have the necessary conditions to prevent potential hazards from contaminating foods. However, little is known about its application in the production of a traditionally fermented and well-patronized food like the Ga kenkey. This study was therefore designed to evaluate the knowledge and practices of Ga kenkey producers in GMPs. A self-administered questionnaire was prepared and used to recruit 42 Ga kenkey producers using convenient sampling techniques. Out of the 42 producers, 83.3% were females, between 18 and 33 years (61.9%) and single (42.9%), and have been in the business for about 0 to 5 years (69.1%). A significant number of producers had neither GMP, food safety nor HACCP training. The producers have inadequate knowledge of GMPs since majority of them do not use gloves and consider wearing them unnecessary. Even though the producers agreed that GMPs improve product qualities, the establishment of reputation, and customer satisfaction and identify problems within the production process, they however did not pay attention to any form of hazards during the production process. Therefore, since education, training, and experience had a significant (P≤0.05) positive influence on the producers’ knowledge and practices, sufficient training in GMPs coupled with regular supervision should be provided to the producers for the hygienic and safe production of this commonly patronized food.